A review of impacts associated with infrastructure news coverage in South Africa. Issue 2 (3rd May 2020) - MacRobert, Charles John
ABSTRACT: The importance of considering both social and environmental impacts of infrastructure development is widely accepted. However, social impacts are often treated in subordination to environmental impacts. This paper examined whether social or environmental impacts dominate public discourse by reviewing 10 years of news coverage by the Mail and Guardian. This found that social impacts dominated news coverage, generated negative emotional responses and more public outrage compared to environmental impacts. At a macro level, this review suggests that social impacts need to receive greater consideration in decision-making. News on power plants was dominated by the economic impacts of insufficient electricity and costs associated with new projects. Social-justice impacts associated with procurement irregularities were also reported. Redressing discriminatory land planning and social-justice impacts caused by the misuse of public finances were the main social impacts associated with housing articles. Impacts on day-to-day activities were often central to articles on water provision, with health-and-wellbeing impacts central to articles on sanitation infrastructure. Articles on roads principally discussed the economic and way-of-life impacts associated with the user-pay principle. Decision-makers will need to consider these social impacts to ensure future project success.